ПРИМЕНЕНИЕ НИКОРАНДИЛА ПРИ СЕРДЕЧНО-СОСУДИСТЫХ ЗАБОЛЕВАНИЯХ И ОПТИМИЗАЦИЯ СХЕМ ЕГО НАЗНАЧЕНИЯ - Ю. Б. Белоусов (SINAPS LLC, 2012)
Nicorandil is a dual pharmacological mechanism anti-anginal agent with adenosinetriphosphat-esensitive potassium (Кatp) channel agonist and nitrate-like properties. The aim of this review is to provide an update on the efficacy of treatment with nicorandil. First, the rationale for nicorandil treatment and its pharmacological effects are reviewed. We explain the mechanisms underlying ischemic preconditioning, with a focus on those that involve the KAТР. Next, clinical practice related lo ischemic preconditioning and pharmacological preconditioning with nicorandil as well as other favourable mechanisms of improvement of prognosis, in which it plays a role in improving endothelial function, modulating autonomic nervous system activity and stabilizing plaque are summarized. Finally, the tolerability of nicorandil is discussed.